Validation of an Enzyme-Driven Model Explaining Photosynthetic Rate Responses to Limited Nitrogen in Crop Plants - Khan, Alamgir; Wang, Zhiwei; Xu, Kang; Li, Liyan; He, Lingchao; Hu, Hanjian; Wang, Genxuan (Frontiers in Plant Science, 2020)
The limited availability of nitrogen (N) is a fundamental challenge for many crop plants. We have hypothesized that the relative crop photosynthetic rate (P) is exponentially constrained by certain plant-specific enzyme activities, such as ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco), NADP-glyceraldehyde-3-phosphate dehydrogenase (NADP-G3PDH), 3-phosphoglyceric acid (PGA) kinase, and chloroplast fructose-1,6-bisphosphatase (cpFBPase), in Triticum aestivum and Oryza sativa. We conducted a literature search to compile information from previous studies on C3 and C4 crop plants, to examine the photosynthetic rate responses to limited leaf [N] levels. We found that in Zea mays, NADP-malic enzyme (NADP-ME), PEP carboxykinase (PCK), and Rubisco activities were positively correlated with P. A positive correlation was also observed between both phosphoenolpyruvate carboxylase (PEPC) and Rubisco activity with leaf [N] in Sorghum bicolor. Key enzyme activities responded differently to P in C3 and C4 plants, suggesting that other factors, such as leaf [N] and the stage of leaf growth, also limited specific enzyme activities. The relationships followed the best fitting exponential relationships between key enzymes and the P rate in both C3 and C4 plants. It was found that C4 species absorbed less leaf [N] but had higher [N] assimilation rates (Arate) and higher maximum photosynthesis rates (Pmax), i.e., they were able to utilize and invest more [N] to sustain higher carbon gains. All C3 species studied herein had higher [N] storage (Nstore) and higher absorption of [N], when compared with the C4 species. Nstore was the main [N] source used for maintaining photosynthetic capacity and leaf expansion. Of the nine C3 species assessed, rice had the greatest Pmax, thereby absorbing more leaf [N]. Elevated CO2 (eCO2) was also found to reduce the leaf [N] and Pmax in rice but enhanced the leaf [N] and N use efficiency of photosynthesis in maize. We concluded that eCO2 affects [N] allocation, which directly or indirectly affects Pmax. These results highlight the need to further study these physiological and biochemical processes, to better predict how crops will respond to eCO2 concentrations and limited [N].